(untitled) (Global Journal of Human-Social Science, 2017)
In Bangladesh there are improvements in secondary education by quantitative indicators but satisfactory picture is remained far from the quality The gross deficiency in teaching includes one of the main reasons for poor quality of secondary education There are higher failure rates in Mathematics subject in Secondary School Certificate examination in the last consecutive years An extensive review of research has shown that teachers account to a large extent for student learning and achievement gains For secondary teacher education in Bangladesh there is a one year long training program named as Bachelor of Education B Ed Therefore the study sought to find out the effectiveness of B Ed program on mathematics teachers teaching practices as a means of improving secondary school mathematics in Bangladesh The study was conducted among 38 mathematics teachers trained and untrained selected from 16 secondary schools of Dhaka city using survey method Their classroom teachings were observed as well as mathematics teachers head teachers instructors and principal of Teachers Training College were interviewed The study found that the B Ed trained mathematics teachers 61 possess better teaching skills than their counterpart 50 but the trained mathematics teachers did not exercise the B Ed outcomes fully in actual teaching 3 06 out of 5 There found no relation between teachers personal characteristics and their pedagogical skills This was the first study to investigate the effectiveness of secondary teacher education program within Bangladesh It contributes important insights about secondary teacher education that can be used to inform the professional development of the secondary school mathematics teachers in Bangladesh